TRANSLATION AND LEXICAL–SEMANTIC PROBLEMS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores the main lexical and semantic problems that arise in the process of translation. It discusses the complex relationship between language, meaning, and culture, focusing on issues such as polysemy, synonymy, idioms, and cultural connotations. The paper emphasizes that translation is not a simple word-for-word substitution but an act of interpreting meaning within a specific cultural and linguistic context. It also highlights strategies for achieving equivalence and overcoming challenges related to semantic ambiguity, idiomatic expressions, and cultural differences. Examples from English, Russian, and Uzbek are used to illustrate these issues.